2008
DOI: 10.1002/mc.20470
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and calcium sensing receptor modulates the expression of thymidylate synthase, NAD(P)H:quinone oxidoreductase 1 and survivin in human colon carcinoma cells: Promotion of cytotoxic response to mitomycin C and fluorouracil

Abstract: Ca 2+ and the cell-surface calcium sensing receptor (CaSR) constitute a novel and robust ligand/ receptor system in regulating the proliferation and differentiation of colonic epithelial cells. Here we show that activation of CaSR by extracellular Ca 2+ (or CaSR agonists) enhanced the sensitivity of human colon carcinoma cells to mitomycin C (MMC) and fluorouracil (5-FU). Activation of CaSR up-regulated the expression of MMC activating enzyme, NAD(P)H:quinone oxidoreductase 1 (NQO-1) and down-regulated the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
70
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 27 publications
0
70
0
Order By: Relevance
“…15 Liu et al 15 reported that functional CASR is necessary for tumor suppressive function of vitamin D and that this function is abrogated by knocking down CASR expression. Therefore, from the viewpoint of chemotherapy and/ or chemoprevention using Ca 2 þ and/or vitamin D, the results obtained in this study are important.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15 Liu et al 15 reported that functional CASR is necessary for tumor suppressive function of vitamin D and that this function is abrogated by knocking down CASR expression. Therefore, from the viewpoint of chemotherapy and/ or chemoprevention using Ca 2 þ and/or vitamin D, the results obtained in this study are important.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,15 To assess the effect of Ca 2 þ on the cytotoxic response to drugs, the medium of cells was replenished with a medium containing physiological concentrations of Ca 2 þ (1.4 mM) and 5-FU (15 mM). The medium of a parallel set of cultures was replenished with a medium only containing 5-FU without the addition of exogenous Ca 2 þ .…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…In colon cancer, welldifferentiated carcinoma cells express observable levels of CaSR, whereas undifferentiated carcinoma cells have little or no CaSR expression (7-10). Since undifferentiated status is one of the mechanisms underlying drug resistance, we have hypothesized in our previous studies that CaSR is involved in chemosensitivity of human colon carcinoma cells and found that activation or induction of CaSR in the cells significantly promoted the sensitivity of the cells to anticancer drug treatment (11,12).The human CaSR gene has two promoters (P1 and P2) and each promoter has a transcriptional start site (4,13-15). Both promoters contain the vitamin D (VD) response element (VDRE), which is recognized and bound by the complex of VD receptor (VDR) activated and bound by VD (15).…”
mentioning
confidence: 99%